BiOBr flakes decoration and structural modification for CdTe/TiO2 spheres: Towards water decontamination under simulated light irradiation. (April 2019) - Qu, Xiaofei; Liu, Meihua; Li, Longfei; Wang, Rui; Sun, Hang; Shi, Liang; Du, Fanglin
Abstract: Utilizing more solar energy and suppressing recombination of photo-induced charges are primary issues for photocatalyst's design. In this work, BiOBr was introduced into CdTe/TiO2 to construct a novel ternary BiOBr/CdTe/TiO2 composite via a facile solvothermal method. The composition, morphologies, optical properties, specific area, and photocatalytic performances were all investigated in detail. The heterojunction among three-dimensional TiO2 particles, BiOBr and CdTe acts an interfacial channel to boost the charges migration. As a result, the ternary BiOBr/CdTe/TiO2 heterojunctions exhibited higher visible light photocatalytic activities on photo-decolorization of methyl orange (MO) than the pure TiO2 and the binary CdTe/TiO2 and BiOBr/TiO2 . Furthermore, the ternary BiOBr/CdTe/TiO2 composites were converted into hollow structure, and showed the better photocatalytic performance, reaching 75% degradation towards MO in 120 min. This study provided an attractive thought to design highly efficient photocatalysts, which possessed a promising for wastewater purification.